Pengaruh Model Problem Based Learning terhadap Hasil Belajar Tematik Kelas V SDN 39 Pontianak Kota - Putri, Adelia Kurnia; Halidjah, Siti; Salimi, Asmayani (AS-SABIQUN, 2023)
The implementation of problem-based learning used in this research suitable for V at State Elementary School 39 Pontianak Kota, where students are expected to achieve thematic learning outcomes. This research used quasi-experimental design type non-equivalent Elementary control group design. All fifth grade students from State Elementary School 39 Pontianak Kota participated in the study. Cluster random sampling was used to determine the sample size. The data collection technique were achieved through a written test consisting of multiple choice and then measured using this method. According to the subject analysis, the average of the reference class was 73.30 and the average of the test class was 80.16. The t-test results used for hypothesis testing (polled variance) were tcount = 2.322 with dk (33+31-2 = 62) and ttable = 1.994 with a significant level = 5%, indicating that tcount > ttable, and Ha is accepted. The evidence shows that problem-based learning could increase students' educational outcomes. An ES of 0.62 is an example of an effect that falls into the category of medium effects. As a result, application of the problem-based learning in class V of State Elementary School 39 Pontianak Kota has a positive effect on improving student learning outcomes in thematic learning.